EFEK NIGELLA SATIVA OIL TERHADAP UKURAN DIAMETER ULKUS TRAUMATIKUS PADA MALE WISTAR RATS SECARA IN VIVO - Linda Septiana; Ratnawati Hendari; Erwid Fatchur Rahman; Diyah Fatmasari (ODONTO : Dental Journal, 2016)
Background: Ulcer is a pathological condition characterized by loss of epithelial tissue. Ulcer will experience healing within 2 weeks after trauma source is removed. Nigella sativa Oil has been known to heal wounds. The purpose of this study was to evaluate the effect of NSO on healing of ulcers in male wistar rats from the use of chemicals.Method: This study design was quasi-experimental methods. Ten male wistar rats were exposing the H2O2 on the mandibular anterior gingiva. divided into negatif control group and NSO group. NSO group treated twice daily for 10 days. Observaton wound size was measured on 0, 3,7, 10 days. The results were analayzed with Repeated Anova test and LSD test.Result: The observations difference diameter of traumatic ulcer negative control group and NSO on 0-10 days was 1.458 mm and 2.182 mm. The results of data analysis showed that there are significant differences (p<0,05) between negatif control group and NSO.Conclusion: NSO has an influence of the size reduction of the diameter of traumatic ulcers.